2019
DOI: 10.1155/2019/2030735
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Radiation Exposure in Patients with Inflammatory Bowel Disease

Abstract: Background. Because of the chronic and relapsing nature of inflammatory bowel disease (IBD), which often requires characterization with CT scan, IBD patients might be exposed to a large amount of radiation. As a cumulative effective dose (CED) ≥ 100 mSv is considered significant for stochastic risks of cancer, it is important to monitor and control the radiation exposure of the IBD patients. In the present work, we aimed to quantify the mean CED in IBD patients to assess any harmful effects of radiation. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…In this study, they obtained a much higher dose of radiation than patients with UC. The range of mean CED in available studies was reported as 14.3–27.5 mSv and 3.65–6.8 mSv for CD and UC patients, respectively [ 3 , 11 , 12 , 13 ], which is consistent with results of our study. Higher radiation exposure among CD patients compared to patients with UC represents the biology of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, they obtained a much higher dose of radiation than patients with UC. The range of mean CED in available studies was reported as 14.3–27.5 mSv and 3.65–6.8 mSv for CD and UC patients, respectively [ 3 , 11 , 12 , 13 ], which is consistent with results of our study. Higher radiation exposure among CD patients compared to patients with UC represents the biology of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…Median radiation exposure among IBD patients ranges from 7.2 to 26.6 mSv for CD patients and from 2.8 to 10.5 mSv for UC patients [ 10 ]. The cutoff level for the definition of a high radiation dose differed between existing studies, which defined it as 50, 75, or 100 mSv [ 8 , 9 , 22 , 23 ]. The percentage of CD compared with UC might influence the choice of different cutoffs for high radiation doses.…”
Section: Discussionmentioning
confidence: 99%
“…Nguyen et al [ 7 ] reported a population-based cohort of IBD patients from Canada between 1994 and 2016 and found Crohn’s disease patients were more likely than UC patients to have excessive radiation exposure (15.6% vs. 6.2%; p < 0.001). Although these previous studies show an increased risk of cumulated radiation exposure among IBD patients [ 7 , 8 , 9 , 10 , 11 ], no previous report addressed this issue among the Taiwanese population. As the incidence and prevalence of IBD are increasing in Taiwan [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ], it is essential to understand the pattern of radiation exposure in this growing population.…”
Section: Introductionmentioning
confidence: 99%
“…Despite recommendations to avoid such investigations in patients with functional gastrointestinal disorders (FGID), widespread use persists in clinical practice, primarily to exclude alternative causes for symptoms. 4,[17][18][19][20][21] Ultrasound (US) represents a novel diagnostic modality in the assessment of FGID. Technological advancements in US have improved its utility in evaluating intestinal contents and faecal loading, incorporating assessment of bowel distension, gas and acoustic shadowing.…”
Section: Introductionmentioning
confidence: 99%
“…Computed tomography and magnetic resonance imaging are more accurate; however, their use is limited by ionising radiation exposure and expense. Despite recommendations to avoid such investigations in patients with functional gastrointestinal disorders (FGID), widespread use persists in clinical practice, primarily to exclude alternative causes for symptoms 4,17–21 …”
Section: Introductionmentioning
confidence: 99%